The character of war in the 21st century - Holmqvist-Jonsater, Caroline; Coker, Christopher (LSE international studies, 2010)
This edited volume addresses the relationship between the essential nature of war and its character at the beginning of the twenty-first century. The focus is on the conflicts in Iraq and Afghanistan, situations that occupy a central role in international affairs and that have become highly influential in thinking about war in the widest sense. The intellectual foundation of the volume is Clausewitz's insight that though war has an enduring nature, its character changes with time, space, social structure and culture. The fact that war's character varies means that different actors may interpret, experience and, ultimately, wage war differently. The conflict between the ways that war is conceptualised in the prevailing Western and international discourse, and the manner in which it plays out on the ground is a key discussion point for scholars and practitioners in the field of international relations. Contributions combine insights from social theory, philosophy, sociology and strategic studies and ask directly what contemporary war is, and what the implications are for the future. This book will be of much interest to students of war studies, strategic studies, security studies and IR in general.